Estimation of allele-specific Ace-1 duplication in insecticide-resistant Anopheles mosquitoes from West Africa. (December 2015) - Djogbénou, Luc; Assogba, Benoît; Essandoh, John; Constant, Edi; Makoutodé, Michel; Akogbéto, Martin; Donnelly, Martin; Weetman, David
Abstract Background Identification of variation inAce -1 copy number and G119S mutation genotype from samples ofAnopheles gambiae andAnopheles coluzzii across West Africa are important diagnostics of carbamate and organophosphate resistance at population and individual levels. The most widespread and economical method, PCR–RFLP, suffers from an inability to discriminate true heterozygotes from heterozygotes with duplication. Methods In addition to PCR–RFLP, in this study three different molecular techniques were applied on the same mosquito specimens: TaqMan qPCR, qRTPCR and ddPCR. To group heterozygous individuals recorded from the PCR–RFLP analysis into different assumptive genotypes K-means clustering was applied on the Z-scores of data obtained from both the TaqMan and ddPCR methods. The qRTPCR analysis was used for absolute quantification of copy number variation. Results The results indicate that most heterozygotes are duplicated and that G119S mutation must now be regarded as a complex genotype ranging from primarily single-copy susceptible Glycine homozygotes to balanced and imbalanced heterozygotes, and multiply-amplified resistant Serine allele homozygotes. Whilst qRTPCR-based gene copy analysis suffers from some imprecision, it clearly illustrates differences in copy number among genotype groups identified by TaqMan or ddPCR. Based on TaqMan method properties, and by coupling TaqMan and ddPCR methods simultaneously on the same type of mosquito specimens, it demonstrated that the TaqMan genotype assays associated with the K-means clustering algorithm could provide a useful semi-quantitative estimate method to investigate the level of allele-specific duplication in mosquito populations. Conclusions Ace -1 gene duplication is evidently far more complex inAn. gambiae andAn. coluzzii than the better-studied mosquitoCulex quinquefasciatus, which consequently can no longer be considered an appropriate model for prediction of phenotypic consequences. These require urgent further evaluation inAnopheles . To maintain the sustained effectiveness carbamates and organophosphates as alternative products to pyrethroids for malaria vector control, monitoring of duplicated resistant alleles in natural populations is essential to guide the rational use of these insecticides.